Efficacy and safety of canagliflozin as add‐on therapy to teneligliptin in Japanese patients with type 2 diabetes mellitus: Results of a 24‐week, randomized, double‐blind, placebo‐controlled trial - Kadowaki, Takashi (Diabetes Obes Metab, 2017)
AIMS: To investigate efficacy and safety of the sodium–glucose co‐transporter 2 (SGLT2) inhibitor canagliflozin administered as add‐on therapy to the dipeptidyl peptidase‐4 (DPP‐4) inhibitor teneligliptin in patients with type 2 diabetes mellitus (T2DM). MATERIALS AND METHODS: We conducted a multicentre, randomized, double‐blind, placebo‐controlled, phase 3 clinical trial in Japanese patients with T2DM who had inadequate glycaemic control with teneligliptin. Patients were randomized to receive teneligliptin 20 mg plus either canagliflozin 100 mg (T + C, n = 70) or placebo (T + P, n = 68) once daily. The primary endpoint was the change in glycated haemoglobin (HbA1c) from baseline to week 24. Other endpoints included changes in fasting plasma glucose, body weight, proinsulin/C‐peptide ratio, homeostatic model assessment 2‐%B and adverse events. Patients also underwent mixed‐meal tolerance tests. RESULTS: The difference between the T + C and T + P groups for HbA1c change from baseline to week 24 was −0.88% (least‐squares mean, P < .001). Fasting plasma glucose, body weight and the proinsulin/C‐peptide ratio were significantly lower in the T + C group than in the T + P group. Homeostatic model assessment 2‐%B improved with T + C compared with T + P. The T + C group exhibited a decrease in the 2‐hour postprandial plasma glucose and plasma glucose area under the curve (AUC)(0‐2h) in a mixed‐meal tolerance test. No significant between‐group differences were observed for C‐peptide AUC(0) (‐2h) or glucagon AUC(0) (‐2h) after meals. Incidences of adverse events were 60.0% and 47.1% in the T + C and T + P groups, respectively. No hypoglycaemia was observed. CONCLUSIONS: Canagliflozin administered as add‐on therapy to teneligliptin was effective and well tolerated in Japanese T2DM patients.